A CONCEPTUAL PAPER OF ISLAMIC NEIGHBOURHOOD PRINCIPLES - Mohd Arip, Mohd Sabri; Teriman, Suharto; Rashid, Kushairi; Ahmad, Aizazi Lutfi; Azman, Muhamad Azrul Azwan (Jurnal 'Ulwan, 2023)
Most neighbourhoods in Malaysia are currently developed and promoted as sustainable, green and eco neighbourhood. It is done to attract the buyers to buy these types of housing schemes and live in a sustainable and liveable manner. However, nowadays the concept of Islamic neighbourhood has been neglected even though most of the residents are Muslim. Besides, there is also a dearth of clear principles that constitute an Islamic neighbourhood. This problem has brought to a lack of understanding amongst researchers, policy makers and housing industry players. Islamic neighbourhood is an important mechanism to ensure a Muslim can live by the Quranic teachings and the Prophet (PBUH)’s sunnah. Thus, the main objective of this study is to identify these Islamic neighbourhood principles through literature review and previous research done at the local and international level. Literature review has been adopted as the main research strategy for this study in reviewing articles, journal, guidelines, reports, and policies documents that are related to Islamic neighbourhood principles. The findings of this study have shown that Islamic neighbourhood consists of five main principles namely land use, social, privacy, housing, and management. These findings have formed an important guideline for policy makers, developers, architect, engineers, planners, industry players and the community itself in planning and developing Islamic neighbourhood. Hopefully, this study is beneficial for more planning and development of Islamic neighbourhood concept that can bring happiness and harmony to multi racial society in Malaysia and other Muslim and non-Muslim countries around.